Family Size And Educational Level Of Parent As Correlates Of Child Abuse Among Teenagers In Mbo Local Government Area (Czech Journal of Multidisciplinary Innovations, 2024)
The study assessed the family size and educational level of parent in relationship to child abuse among teenagers in Mbo Local Government Area. In carrying out the study, a survey research design was adopted for this study. The study was carried out in Mbo Local Government Area. The targeted population for the study comprised all teenagers in Mbo local government area of Akwa Ibom State. A simple random sampling technique was used to select a total of 220 teenagers for the study. The instrument used for data collection was a structured questionnaire titled “Social Variables and Child Abuse Questionnaire (SVCAQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement, and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.83, and this was high enough to justify the use of the instrument. The researcher subjected the data generated for this study to appropriate statistical techniques such as descriptive statistics meant to answer the research questions and simple regression analysis meant to test the hypothesis. The test for significance was done at 0.05 alpha levels. Based on the findings of the work it can be concluded that the educational status of the parent, family size, and income level of the parent have significant effect on child abuse among teenagers in Mbo Local Government Area. This in turn contributes immensely to engagement in robbery, and rapes. One of the recommendations made was that government at all level should encourage on family planning in order to help control rate of child bearing to a bearable size to avert child labour.